Multiple First Order Transitions in Cr Thin Films - Rodriguez, R. H.II Tosi, L.IIMenghini, M.II Pastoriza, H.IIBalseiro, C. A. (2014)
Fil: Rodriguez, R. H. Comisión Nacional de Energía Atómica. Instituto Balseiro; ArgentinaIIFil: Tosi, L. Comisión Nacional de Energía Atómica. Instituto Balseiro; ArgentinaIIFil: Pastoriza, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; ArgentinaIIFil: Balseiro, C. A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina